Non-pharmacological interventions for reducing anxiety and depression symptoms among adolescents and young adults: Protocol for a scoping review - Gerald Agyapong-Opoku; Belinda Agyapong; Temitayo Sodunke; Ejemai Eboreime; Andrew Greenshaw (PLoS ONE, 2026)
Background Anxiety and depression are leading causes of mental health-related disability among adolescents and young adults worldwide. These conditions often begin in adolescence and can persist into adulthood, with long-term consequences for individuals’ well-being, education, and social functioning. Although a growing number of interventions have been developed to address these concerns, they vary widely in format, setting, and target population. Objective This scoping review aims to systematically map the range and characteristics of interventions targeting anxiety and depression among adolescents and young adults aged 10–24. Methods This scoping review will be conducted following the Joanna Briggs Institute (JBI) methodological guidance for scoping reviews and reported in accordance with the PRISMA-ScR checklist. A comprehensive search will be undertaken across several electronic databases (PubMed, PsycINFO, Scopus, CINAHL, Web of Science, and Embase). Eligible studies will include any empirical research focused on interventions aimed at reducing symptoms of anxiety or depression among individuals aged 10–24 years. Two independent reviewers will select and chart the studies, and findings will be summarized using descriptive and thematic analysis. Results The findings will provide an overview of interventions adopted to reduce anxiety and depression among adolescence across diverse settings, identify the most popular or commonly accepted interventions among this cohort and its modalities. The findings will also highlight the need for stakeholders and policymakers to support the design, implementation, and evaluation of targeted mental health strategies for adolescents and young adults. Dissemination Findings will be published in a peer-reviewed journal and shared with stakeholders including researchers, clinicians, and policymakers. The results will inform future research, intervention development, and policy planning aimed at supporting the mental health of adolescents and young adults.